Analisis Perilaku Konsumsi terhadap Kartu Kredit PT. Bank Rakyat Indonesia (Persero) TBK Wilayah Sumba Barat - Elvina Cresentia Ham; Bambang Budiarto; Joshi Maharani Wibowo (Syntax Idea)
This study aims to analyze consumption behavior towards the use of PT Bank Rakyat Indonesia (BRI) credit cards. This research uses a quantitative approach by collecting data through an online survey to BRI credit card holders. The sample of this study consisted of 32 respondents who were randomly selected. The variables analyzed include factors that influence credit card consumption behavior, such as income, perceptions of credit cards, shopping habits, gender, age, occupation and credit card usage preferences. The purpose of this research is to see how influential the lifestyle and environment in West Sumba Regency which can be said to be still developing, this research uses a descriptive qualitative approach.